2016
DOI: 10.1039/c6dt01982j
|View full text |Cite
|
Sign up to set email alerts
|

Tetracarbalane structures: nido polyhedra and non-spherical deltahedra

Abstract: Uhl and coworkers have synthesized and characterized structurally the 11-vertex tetracarbalanes (AlMe)7(CEt)4(μ-H)2 and (AlEt)7(CCH2Ph)4(C[triple bond, length as m-dash]CPh)(μ-H). In order to understand the nature of the unusual C4Al7 polyhedra in such systems, the complete series of permethylated tetracarbalanes C4Aln-4Men (n = 6 to 14) as model compounds have been investigated using density functional theory. An overriding factor in determining the polyhedra for the lowest energy structures of a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The significantly larger covalent radius of indium (1.42 Å) relative to that of gallium (1.22 Å) [53] leads to major differences in the low-energy struc- The cyclic C 4 tetragon found in a few low-energy tetracarbindane clusters is a new structural motif not found in any of the previously studied low-energy tetracarbalane [12] and tetracarbagallane [13] structures. Such C 4 tetragons are essentially trapezoids with two nearly equivalent C C distances of 1.49 ± 0.02 Å, a significantly longer C C distance of 1.57 ± 0.03 Å, and a short C C distance of 1.37 ± 0.02 Å corresponding to a formal double bond.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The significantly larger covalent radius of indium (1.42 Å) relative to that of gallium (1.22 Å) [53] leads to major differences in the low-energy struc- The cyclic C 4 tetragon found in a few low-energy tetracarbindane clusters is a new structural motif not found in any of the previously studied low-energy tetracarbalane [12] and tetracarbagallane [13] structures. Such C 4 tetragons are essentially trapezoids with two nearly equivalent C C distances of 1.49 ± 0.02 Å, a significantly longer C C distance of 1.57 ± 0.03 Å, and a short C C distance of 1.37 ± 0.02 Å corresponding to a formal double bond.…”
Section: Discussionmentioning
confidence: 88%
“…The theoretical methods used in this study are similar to those in our recently reported studies on the analogous tetracarbalanes and tetracarbagallanes . Thus, the initial model structures were based on various In n Me n polyhedral frameworks in which a systematic substitution of four indium atoms by four carbon atoms led to 1365 starting structures of the type C 4 In n−4 Me n (n = 6‐14) (see the Supporting information).…”
Section: Theoretical Methodsmentioning
confidence: 95%
See 3 more Smart Citations